PENERAPAN MODEL PARTNERS IN LEARNING UNTUK MENINGKATKAN KOLABORASI DAN PRESTASI BELAJAR - Eva Efriani (DIADIK, 2024)
The aims of this study are to: (1) describe the increase in student collaboration in English subjects through the application of the Partners in Learning Model, (2) describe the increase in student achievement in English subjects through the implementation of the Partners in Learning Model, (3) describe the effectiveness of the implementation of the Partners in Learning model can improve the English learning achievement of eighth grade students of SMP Negeri 4 Community of Lahat Regency. This study used the Classroom Action Research (CAR) method and continued with experimental research. The subjects of this study were class VIII students who were in SMP Negeri 2 PSEKSU Lahat Regency for the PTK class and students of class VIII.1 for the experimental class and class VIII.2 for the control class which was held at SMP Negeri 1 Gumay Talang. Data collection techniques used are observation sheets and tests. The research data were analyzed by descriptive statistics, average (mean), percentage, and t-test. The conclusions of this research are; (1) The application of the Partners in Learning model can increase student collaboration in English subjects. (2) The application of the Partners in Learning model can improve student achievement in English subjects at Community Junior High School 4 Lahat Regency and (3) The application of the Partners in Learning model is effective in improving students' learning achievement